Company Financial Performance Before and During The Covid-19 Pandemic - Putra, Ferdy; Khoiriyah, Mayla; Abdurrahman, Rezi; Fatriansyah, Alif Ilham Akbar (Universitas Muhammadiyah Semarang, 2023)
This research aims to examine how liquidity, leverage, activity, and growth influence company financial performance before and during the COVID-19 pandemic. This research used purposive sampling with a population of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019 for the period before the COVID-19 pandemic and in 2020 during the COVID-19 pandemic obtained 279 observations. Data were analyzed using SPSS 26. The results showed that Liquidity significantly affected the company's financial performance before the COVID-19 pandemic. In contrast, it has a significant negative effect on ROA, an insignificant negative effect on ROE and an insignificant positive effect on Tobin's q during the COVID-19 pandemic. Leverage has significant adverse effects before and during the COVID-19 pandemic. Activity had a significant positive effect before the COVID-19 pandemic, while it had a non-significant positive effect during the COVID-19 pandemic. Growth had a significant positive effect before the COVID-19 pandemic, a non-significant positive effect on ROA and ROE, and an insignificant negative effect on Tobin's q during the COVID-19 pandemic. Companies should pay attention to the leverage ratio because leverage has a significant negative influence before and during COVID-19, which means leverage can significantly reduce financial performance. For this reason, the company must regulate the capital structure following the company's capabilities.